PEMBINAAN MENTAL SPIRITUAL AL-ISLAM KEMUHAMMADIYAHAN BAGI MAHASISWA SEMESTER 2 PENDIDIKAN BAHASA ARAB FAKULTAS AGAMA ISLAM. - Ahmad Helwani; Ahadiah Agustina; Nurjannah Nurjannah (El-Khidmat, 2024)
The aim of the Community Partnership Program (PKM) is to provide understanding and knowledge about Al-Islam and Kemuhammadiyahan to semester 2 students in the Arabic Language Education Study Program, Faculty of Islamic Religion, University of Muhammadiyah. The methods used are lectures (coaching), training, Focus Group Discussion (FGD) and mentoring to participants. A grant of one million rupiah in the form of coaching and providing reference books on Al-Islam and Muhammadiyah. The goal is that the coaching can be used as a provision for da'wah. Indicators of success in the short term can be seen from the activeness of the management of Islamic economic associations in FGD activities and asking questions about the technical implementation of Sharia-based financial services to the service team. Indicators of long-term success will be measurable in the next few years in line with the activities of the development and existence of Muhammadiyah